Contribution of monocarboxylate transporter 12 to blood supply of creatine on the sinusoidal membrane of the hepatocytes - Jomura, Ryuta; Tanno, Yu; Akanuma, Shin-ichi; Kubo, Yoshiyuki; Tachikawa, Masanori; Hosoya, Ken-ichi (American journal of physiology: Gastrointestinal and liver physiology, 2021)
Our study is the first to identify the role of monocarboxylate transporter 12 (MCT12) as a transporter of creatine (Cr) in the liver. MCT12 was found to significantly contribute to the efflux of Cr on the sinusoidal membrane of the hepatocytes. Since hepatocytes are known to be involved in creatine biosynthesis. The present findings can be beneficial for the regulation of Cr biosynthesis and supply. Creatine (Cr)/phosphocreatine has the ability to buffer the high-energy phosphate, thereby contributing to intracellular energy homeostasis. As Cr biosynthetic enzyme deficiency is reported to increase susceptibility to colitis under conditions of inflammatory stress, Cr is critical for maintaining intestinal homeostasis under inflammatory stress. Cr is mainly produced in the hepatocytes and then distributed to other organs of the body by the circulatory system. Since monocarboxylate transporter 9 (MCT9) and monocarboxylate transporter 12 (MCT12) have been reported to accept Cr as a substrate, these transporters are proposed as candidates for Cr efflux transporter in the liver. The aim of this study was to elucidate the transport mechanism on Cr supply from the hepatocytes. Immunohistochemical staining of the rat liver sections revealed that both MCT9 and MCT12 were localized on the sinusoidal membrane of the hepatocytes. In the transport studies using Xenopus laevis oocyte expression system, [ 14 C]Cr efflux from MCT9- or MCT12-expressing oocytes was significantly greater than that from water-injected oocytes. [ 14 C]Cr efflux from primary cultured hepatocytes was significantly decreased following MCT12 mRNA knockdown, whereas this efflux was not decreased after mRNA knockdown of MCT9. Based on the extent of MCT12 protein downregulation and Cr efflux after knockdown of MCT12 in primary cultured rat hepatocytes, the contribution ratio of MCT12 in Cr efflux was calculated as 76.4%. Our study suggests that MCT12 substantially contributes to the efflux of Cr at the sinusoidal membrane of the hepatocytes. NEW & NOTEWORTHY Our study is the first to identify the role of monocarboxylate transporter 12 (MCT12) as a transporter of creatine (Cr) in the liver. MCT12 was found to significantly contribute to the efflux of Cr on the sinusoidal membrane of the hepatocytes. Since hepatocytes are known to be involved in creatine biosynthesis, the present findings can be beneficial for the regulation of Cr biosynthesis and supply.